TURNOVER AUDITOR DI KANTOR AKUNTAN PUBLIK - Dwi Prihatini (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2022)
KAP XYZ, is one of the big four Public Accounting Firms (KAP) located in Jakarta. provides higher remuneration compared to other firms or KAP. Therefore, it attracts accounting fresh graduates to apply for a job at KAP XYZ . However, the turnover rate or auditor turnover is considered high and this research will explore the reasons why many auditors resign from KAP XYZ which makes high turnover every year. The research methodology is in the form of qualitative descriptive research with data collection in the form of literature studies, observations and interviews. The selection of informants was carried out by means of purposive sampling. The results of research on what causes auditor turnover are as follows: getting attractive offers at other companies, continuing studies domestically or abroad, having careers in other fields and outside of auditing/accounting as employees or self-employed, stoppin a career due to household or other reasons family, team situation, burnout, work life balance, high salary and benefits but working long hours, working long hours and inappropriate overtime wages, overloaded workload and detailed work.Keywords : Auditor, Turnover, Big Four, KAP, Causes of resignation